Ketahanan Membran Komposit Kitosan/ Polisulfon Terhadap pH - Erna, Maria; Haryati, Sri; Naldo, Roy; Yana, Yeni Fitri (Universitas Andalas, 2008)
ABSTRACT It has been done resistance test of chitosan/polysulfon composite membrane to solvent. The results of research obtained that resistance composite membrane to pH. This matter is marked with its percentage swelling highest that is 75.48%. This result is also supported by porous photo membrane using SEM that is across-section, up surface and bottom photo showed that happed change porous structure membrane but structure tying membrane can not experiencing of damage. Keywords: composite membrane, chitosan, percentage of swelling